Implementasi Punishment dalam Meningkatkan Tanggung Jawab Belajar PAI pada Siswa UPT SMP Negeri 17 Medan - Naibaho, Putri; OK, Azizah Hanum (LPPM Institut Pendidikan Nusantara Global, 2025)
This research method uses a qualitative approach with a phenomenological approach. This approach was chosen to understand students' subjective experiences related to the implementation of punishment in the context of Islamic Religious Education (PAI) learning responsibilities. The data collection process was carried out through in-depth interviews with students, teachers, and schools involved in the implementation of punishment. This interview aims to explore their views, feelings, and experiences regarding the effects of punishment on students' learning responsibilities. In addition, classroom observations were also conducted to see the dynamics of interactions between students and teachers and the implementation of punishment in real situations. The data obtained were analyzed using thematic analysis techniques, where researchers identified the main themes that emerged from interviews and observations. This process involves coding data, grouping themes, and interpreting the meaning of the experiences expressed by participants. With a phenomenological approach, this study seeks to provide a deep understanding of how punishment affects students' learning responsibilities in PAI, as well as how students and teachers respond to and interpret these experiences. The results of this study are expected to provide valuable insights for the development of more effective educational strategies in the context of PAI learning.